2006
DOI: 10.1158/1078-0432.ccr-06-1546
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Specific T-Cell Immune Responses in Patients Vaccinated with Truncated HER2 Protein Complexed with Nanogels of Cholesteryl Pullulan

Abstract: Purpose: We developed a complex of tumor antigen protein with a novel nanoparticle antigen delivery system of cholesteryl pullulan (CHP). To target HER2 antigen, we prepared truncated HER2 protein 1-146 (146HER2) complexed with CHP, the CHP-HER2 vaccine. We designed a clinical study to assess the safety of the vaccine and HER2-specific T-cell immune responses measured by the newly developed enzyme-linked immunospot assay with mRNA-transduced phytohemagglutinin-stimulated CD4 + T cells in HLA-A2402-positive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 19 publications
1
78
0
Order By: Relevance
“…Although there are only very limited data on the effect of multiple cycles of vaccination in humans, a few studies support the idea of progressive strengthening of tumor-specific immunity over prolonged courses of vaccination (18,20,44). As we observed in this study with broadening of immune responses upon repeated vaccination, the application of serial vaccinations might indeed improve the immunological, and hopefully also clinical, efficacy of cancer vaccines.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Although there are only very limited data on the effect of multiple cycles of vaccination in humans, a few studies support the idea of progressive strengthening of tumor-specific immunity over prolonged courses of vaccination (18,20,44). As we observed in this study with broadening of immune responses upon repeated vaccination, the application of serial vaccinations might indeed improve the immunological, and hopefully also clinical, efficacy of cancer vaccines.…”
Section: Discussionsupporting
confidence: 59%
“…We also detected MAGE-A3-specific CD8 ϩ T cell responses in patients who developed the highest-titered broadly specific antibody responses after vaccination. So far, few trials have been conducted in which recombinant proteins were used as immunogen in cancer vaccines (12)(13)(14)(15)(16), and if T cell responses have been reported, they consisted mainly of CD4 ϩ T cells (17,18). Two reports have shown that vaccination with CT antigen NY-ESO-1 as a recombinant protein, formulated either with saponin-based adjuvant ISCOMATRIX or with cholesterol-bearing hydrophobized pullulan, induced strong antibody as well as CD4 ϩ and CD8 ϩ responses in the majority of patients (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] A number of methods for targeting antigens to LN macrophages have been investigated as part of the ongoing development of lymphatic-targeted vaccines. It was reported that cholesteryl pullulan (CHP) nanogels induce tumor regression in some patients with malignant tumors, 29,30 and CD169-positive macrophages in LN sinus captured CHP nanogels and worked as APCs. 31 Thus, lymphatic-targeting materials might be a promising approach to improving vaccine efficacy, and CD169-positive macrophages are now of interest as APCs to which antigens might be efficiently delivered.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Both CD4 and CD8 T cells are efficiently activated by DCs pulsed with a complex of CHP and NY-ESO-1 protein (CHP-NY-ESO-1) in vitro.…”
mentioning
confidence: 99%